Adenosine deaminase 2 deficiency with a novel variant of CECR1 gene mutation: Responding to tumor necrosis factor antagonist therapy - Zakiya Saleh Al Mosawi; Hiba Omar Abduljawad; Maryam Yusuf Busehail; Barrak Mahmood Al Moosawi (Indian Journal of Rheumatology)
Deficiency of Adenosine deaminase 2 (DADA2) syndrome is a chronic, systemic, and inflammatory disorder, characterized by early-onset recurrent strokes, fever, livedo reticularis, and immunodeficiency. We report the case of a 4-year-old child, a product of consanguineous marriage, who presented with three episodes of hemiparesis within 1 year. She also manifested skin discoloration in the form of livedo reticularis. Workup with magnetic resonance imaging (MRI) of the brain revealed acute infarction in the right aspect of the cerebral peduncle and chronic lacunars infarct in the right thalamus with diffusion restriction. Repeated MRI after 5 months revealed diffuse loss of brain volume. The blood workup showed high inflammatory markers and significantly low adenosine deaminase 2 (ADA2) level. After being on corticosteroid and anticoagulant treatments, she suffered from a recurrent episode of cerebral infarction, after which she was commenced on tumor necrosis factor (TNF)-antagonist therapy in addition to monthly fresh plasma infusion. Thereafter, there was no cerebral insult reported for >18 months. The genetic study of the child and her parents revealed a homozygous mutation c. 336C>A, p. (His112Gln) in the CECR1 gene, and her parents were heterozygous for the same variant. This variant was not previously reported in literature. We would suggest to link this novel variant c. 336C>A, p. (His112Gln) of CECR1 gene mutation with the clinical picture, along with the positive response to TNF-antagonist therapy in the era of ADA2 deficiency syndrome.